Hubungan Asupan Kalsium dan Indeks Massa Tubuh dengan Kepadatan Tulang pada Wanita Usia Subur - Aini, Nurul; Pratiwi, Amali Rica; Dewi, Afiska Prima; Wati, Desti Ambar (Jurnal Kesehatan, 2022)
In women of childbearing age, the rate of bone formation will decrease gradually. If a bone formation is reduced continuously then it can cause osteoporosis. Insufficient calcium intake and abnormal body mass index can also cause reduced bone density. The purpose of this study was to analyze the correlation between calcium intake and body mass index with bone density in women of childbearing age in the Medical Faculty Universitas Lampung in 2021. This cross-sectional study of 80 respondents consisting of lecturers, employees, and students aged 20-45 years who were selected by purposive sampling was carried out in November-December 2021. Demographic data, Semi Qualitative-Food Frequency Questionnaire (SQ-FFQ), Kris digital scales 9360A, microtoise GEA, and Quantitative Ultrasound (QUS) were used to measure all variables. Spearmen Correlation Test with a significant level of p-value<0.05 was used to see the relationship between variables. The results of the univariate analysis showed that the majority of respondents were aged 20-25 years (76.2%) and college students (78.8%). The average intake of calcium and body mass index was 709.2 and 21.2 and 31 respondents (38.8%) had osteoporosis. The results of the bivariate analysis showed a positive and significant correlation between calcium intake and bone density (p-value=0.000, r=0.687) and bone body mass index with bone density (p-value=0.000, r=0.596). The conclusion, there was a positive and significant correlation between calcium intake and body mass index with bone density in women of childbearing age in the Medical Faculty of Universitas Lampung in 2021.Â